Oral health status and treatment needs of children with sensory deficits: a narrative review - Katkam, Pallavi; Puranik, Manjunath P.; Shanbhag, Namita (International Journal of Research in Medical Sciences, 2024)
Oral health is an inescapable component of overall health. Oral health care and maintenance is an essential component of overall growth and development of children. Inculcating and following good oral hygiene practices with appropriate diet modification is a prerequisite to achieving sound oral health. Oral health is an important aspect of health for all children, and is more important for children with special health needs. Children with sensory deficits deserve the same opportunities for oral health and hygiene as those who are healthy. Unfortunately, oral health care is one of the greatest underserved health needs of disabled people. Inadequate dental care or poor dental public health measurements may have negative influence on their oral health status. Hence this review discusses the types, epidemiology, classification, etiology, clinical features, oral health status, treatment needs and dental management of children with sensory deficits.